The responsibility of the philosopher - Vattimo, Gianni, 1936- (Columbia University Press, 2010)
Over the course of his career, Gianni Vattimo has assumed a number of public and private identities and has pursued multiple intellectual paths. He seems to embody several contradictions, at once defending and questioning religion and critiquing and serving the state. Yet the diversity of his life and thought form the very essence of, as he sees it, the vocation and responsibility of the philosopher. In a world that desires quantifiable results and ideological expediency, the philosopher becomes the vital interpreter of the endlessly complex. As he outlines his ideas about the philosopher's role, Vattimo builds an important companion to his life's work. He confronts questions of science, religion, logic, literature, and truth, and passionately defends the power of hermeneutics to engage with life's conundrums. Vattimo conjures a clear vision of philosophy as something separate from the sciences and the humanities but also intimately connected to their processes, and he explicates a conception of truth that emphasizes fidelity and participation through dialogue.